THE RELATIONSHIP LIFESTYLE AND CENTRAL OBESITY IN CLINICAL STUDENT FACULTY OF MEDICINE CHRISTIAN UNIVERSITY OF INDONESIA IN 2021 - Sanggul Andriyani Risma (JURNAL WIDYA MEDIKA, 2022)
Prevention and control of central obesity is very important to prevent cardiovascular disease. Central obesity is a condition where there is an accumulation of excess fat in the abdominal area so that it looks fat in the stomach and the body shape resembles an apple. Cardiovascular risk increases because fat cells in the abdomen release their fat into the blood vessels. Lifestyle factors such as consumption of fiber foods, physical activity and stress affect the occurrence of central obesity. Objective: This study aims to determine the relationship between lifestyle and the incidence of central obesity in clinical students faculty of medicine Christian University of Indonesia in 2021. Methods: This study used a cross sectional analysis design. Primary data collection was carried out in December 2021-January 2022 in the form of questionnaires distributed to 254 clinical students faculty of medicine UKI in 2021. A total of 156 samples met the inclusion criteria and had complete data and were included in the analysis. The independent variables are age, sex, smoking, stress, diet and physical activity. The dependent variable is central obesity. Results: In the univariate analysis, 72% less physical activity was found, central obesity was 41% and smoking was 15.9%. A total of 95.3% of samples with central obesity have a diet lacking in fiber. In the chi-square analysis, there was a significant relationship between dietary patterns and central obesity (p=0.01). Conclusion: The conclusion of this study is that if we consume less fiber, it will increase the risk of central obesity. Keywords: Central Obesity, lack of fiber, cardiovascular disease